Development of questionnaire for assessment of snack and fast food consumption among urban children aged 7-9 years - Sharif Ishak, Sharifah Intan Zainun (2012)
Snack and fast food consumption has been identified in contributing to the development of childhood obesity. To date, there is a lack of valid and reliable food frequency questionnaire (FFQ) for the assessment of these food items in Malaysia. The present study was aimed to develop a validated and reliable FFQ for the assessment of snack and fast food consumption among 7-9 years old urban children. This study was divided into two phases. Phase 1 which is the development of FFQ using focus group discussions (FGDs)aimed to identify types of snack and fast food usually consumed by children and to develop a preliminary food list for FFQ. A total of 33 children aged 7-9 years old from Selangor and Kuala Lumpur participated in the FGDs. FGDs were audio-taped, transcribed and analyzed. The outcomes showed that the children usually consumed snacks such as white bread with spread or as sandwich, local cakes, fruits such as papaya, mango and watermelon, biscuits or cookies, tea, chocolate drink and instant noodle. Their choices of fast food included pizza, burger, French fries and fried chicken. The reasons of the food liking were the taste, their knowledge on the nutritional values and the characteristics of foods. The preliminary food list was prepared which included 49 food items. Phase 2 is a validity and reliability study of the FFQ conducted in selected schools in Selangor. For face validity, 50 parents were included in the study and the suggestions of the food items to be included in the FFQ were obtained. A total of 67 food items were prepared to be included in the FFQ which consider the parents’ suggestions. To determine the internal validity, we included 424 parents (68.6% mothers) who have completed the FFQ. Out of 67 items, 37 items were retained in the final model. The factor analysis suggested 6 factors that explained 41.84% of the variance. These factors were labelled local fried and savoury snacks, fresh fruits and fruit juice, sweet snacks, sweetened beverages and western-style fast food, bread and bread spread; and cerealbased foods. Internal consistency reliability, assessed by Cronbach’s alpha (α) for all 37 items was high (α=0.883). All 6 factors showed acceptable reliability which ranged from 0.722 (Factor 2: fresh fruits and fruit juice) to 0.864 (Factor 1: local fried and savoury snacks). Test-retest reliability was determined by using paired t-test. There were no significant difference of the frequency of food intake between the first and second questionnaires for most of the factors except for Factor 1 (local fried and savoury snacks) and Factor 3 (sweet snacks). This indicated acceptable test-retest reliability and stability of the responses to the items in the FFQ over time. The prevalence of overweight among 424 children was 14.6%. Most of the children have normal weight status (84.9%) and 0.5% underweight. The mean BMI was 16.2 kg/m2. The developed FFQ has acceptable validity and reliability in urban sample of 7-9 years old school children for the assessment of snack and fast food intake. The FFQ may contribute as one of brief food intake assessment tools specifically for assessing the consumption of snacks and fast food in Malaysian urban children aged 7-9 years old.